دراسة مقارنة لبعض أنواع النعناع من منطقة وادريغ – تقرت - بن بداري, إكرام; قرفي, عقيلة; بوحفص, العطرة; دويس, سارة (University of Eloued جامعة الوادي, 2023)
The aim of this work is a comparative study of some types of mint plant Mentha Spicata Piperita.l Mentha, Mentha Pulegium.l which belong to the Lamiaceae family, from the region of Wadi Reg Toqrat through the detection of the active substances of the types of mint studied, and the extraction of essential oils from them The three samples of mint through the process of water distillation using the Clevenger device, and then estimating the antibacterial and antifungal biological effectiveness by implementing the diffusion method using the standard disc diffusion test, and studying some of the chemical and physical properties of these oils (saponification number, acid number, ester number, refractive index); Where the study showed that the three types of mint plants contained most of the active substances. As for the extraction of oils, their yield was estimated at (Mentha Spicata 1.04% - Piperita.l Mentha 2% - Mentha Pulegium.l 1.82%). Considerable biological for these types of mint Based on the results obtained through this study, it can be concluded that the mint plant with its three types studied has high quality because it contains most of the active substances and also contains a good yield of essential oils that have biological effectiveness
التنوع البيئي والمحيط
Keywords: Mentha mint plant; phytochemical survey; oil extraction; biological activity; physical and chemical factors.; نبات النعناع ، المسح الكيميائي النباتي ، استخلاص الزيت ، البيولوجي النشاط والعوامل الفيزيائية والكيميائية.